DEVELOPMENT OF ENVIRONMENTALLY CONCERNED ISLAMIC RELIGIOUS EDUCATION AT SMPS GENERASI BANGSA MEDAN LABUHAN - Ahmad Maulana; Ali Imran Sinaga; Rusydi Ananda (UIN Sumatera Utara Medan, 2024)
The aim of this research is to analyze the development of Islamic Religious Education with an environmental perspective that is appropriate, practical and effective for use as teaching material. The research method used is development research with the 4-D (Define, Design, Develop dan Dessimination). The subjects in this research were class IX students at SMPS Generasi Bangsa Medan. Data collection instruments are observation, interviews, questionnaires, tests and documentation. The results of the research show: (1) the development of teaching materials is first carried out by performance analysis and needs analysis, then carrying out the design stage, (2) the feasibility of teaching materials is carried out by validation with an average score the overall percentage is 78.7%, valid category, (3) the practicality of the module obtained an overall average percentage score of 85.2%, very practical category, and (4) the effectiveness of teaching materials in improving student learning outcomes obtained a normalized gain score ( N-Gain) 0.55, which is in the effective category.